1977
DOI: 10.1002/chin.197748092
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: DISPROPORTIONATION OF HALOOLEFINS

Abstract: Halogenolefine werden durch Rheniumoxid/Aluminiumoxid allein nicht disproportioniert, da der Katalysator sofort inaktiviert wird.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A tungsten dichlorocarbene complex [W]=CCl 2 has also been proposed as an active species in the W(CO) 6 /CCl 4 / hν catalyst system 9. To our knowledge, there has been only one report of metathesis involving directly halogenated olefins, namely the cross metathesis of 1‐chloro‐ and 1‐bromoethylene with propylene using Re 2 O 7 /Al 2 O 3 /Me 4 Sn 6e. Herein, we report the successful metathesis of 1,1‐difluoroethylene with ruthenium catalyst 1 .…”
Section: Romp Of Cod With Catalysts 1–3[a]mentioning
confidence: 93%
“…A tungsten dichlorocarbene complex [W]=CCl 2 has also been proposed as an active species in the W(CO) 6 /CCl 4 / hν catalyst system 9. To our knowledge, there has been only one report of metathesis involving directly halogenated olefins, namely the cross metathesis of 1‐chloro‐ and 1‐bromoethylene with propylene using Re 2 O 7 /Al 2 O 3 /Me 4 Sn 6e. Herein, we report the successful metathesis of 1,1‐difluoroethylene with ruthenium catalyst 1 .…”
Section: Romp Of Cod With Catalysts 1–3[a]mentioning
confidence: 93%
“…CHz=CHz CH z CH z + ~ I I + II (53) COz=COz CO z CO2 catalysed by Re 2 0 7 /y-AI 2 0 3 • They observed that pretreatment of the catalyst with a higher alkene, e.g. propene, highly improves the catalytic activity.…”
Section: Initiation and Terminationmentioning
confidence: 96%
“…Halogen-containing alkenes also undergo metathesis. Even vinyl halides can be transformed into their metathesis products [53]: 2 CH2 =CH-CI ~ CHz=CHz + CI-CH=CH-CI (27) Silicon-containing alkenes react as easily as simple alkenes, obviously because of the carbon-like chemical behaviour of this hetero-atom [54]; alkenes containing both silicon and oxygen can also undergo metathesis [55].…”
Section: Functionalized Alkenesmentioning
confidence: 99%
“…A further enhancement in activity of the rheniumbased catalyst by a factor of 5-10 can be obtained by adding a tetraalkyltin promoter [78,94,102]. When promoted with a small amount of a tetraalkyltin (R 4 Sn, R = Me, Et or Bu) or a tetraalkyllead (R 4 Sn, R = Et or Bu) compound, all of these modified catalysts bring about the metathesis of alkenes containing functional groups (e.g.…”
Section: Modified Re 2 O 7 /Al 2 O 3 Catalystsmentioning
confidence: 99%